Construction cost comparison between conventional and formwork system for condominium project - Md. Rahim, Mohd Syazwan; Haron, Nuzul Azam (International Association of Academicians, Scholars, Scientists & Engineers, 2013)
Based on recent scenario, Malaysia has emerged towards industrialization in all aspects of development. Most significantly, construction industry in Malaysia has transformed into a transitional paradigm changed, from the conventional system technology towards a more systematically, mechanized and industrialized forms, which adopted the latest and modernized technology. The transformation and innovation of this technology has evolved out of a tremendous backlog in the construction of the commercial and residential buildings. Apparently, the so-called ‘Industrialised Building System’ (IBS) is one of the major constituents in the construction systems. This system has been regulated and varied in a completely different manner compared to the conventional construction system, thus effected the design, construction method statements and most importantly the cost implications (CIDB, 2000). A case study was carried out by the researcher. The data required for this case study was generated through interviews. From the results of the case study, it undertaken can be concluded that the Industrialised Building System is better construction cost saving as compared to the conventional system.